The Effect of Implementation of Elderly Respect Training Program in Families on Elder Abuse in Yazd - Aliakbar Vaezi; Mohammad Hassan Lotfi; Maryam Shaker (Shahid Sadoughi University of Medical Sciences, 2018)
Introduction: The elderly are among the most vulnerable group in the society, and elder abuse is poses a challenge in the domain of elderly care and support. The present study was conducted with the aim of exploring the effect of implementation of an elderly respect education program in families on the elder mistreatment in the city of Yazd in 2016. Methods: The present study was an experimental study of the field trial type that was conducted on 80 elderly people over the age of 65 years who were covered by Yazd Comprehensive Health Service Centers. This sample was randomly divided into two groups: the intervention group (n= 40) and non-intervention group (n= 40).The sampling units were invited for participating in the study through phone call by healthcare providers. Then, the interviewer completed the questionnaire, after introducing himself and giving explanations on the objective of the study. The data collection tool was the Elder Abuse Scale that included 49 items in eight subscales: care neglect, psychological abuse, physical abuse, financial abuse, authority deprivation, rejection and financial and emotional neglect. In the next step, the families of the elderly in the intervention group were invited to participate in the educational program. The content of this program included different elder abuse subjects, the importance of respecting the elderly in the family and the society, and the role of families in supporting and protecting the elderly. One month after the end of the educational program for families, the elderly in both the intervention group and non-intervention group were invited to be interviewed and the questionnaire was completed. Data analysis was done using software SPSS and through the independent t-test and chi-squared test. Results: Analysis of the mean of elder abuse dimensions in the intervention group indicated that there was a significant difference between the scores before and after the intervention (P< 0.05).The study of the mean of abuse dimensions in the elderly non-intervention group, no significant difference was seen before and after the intervention (P> 0.05). The highest level of abuse was seen in the dimension of emotional neglect and the lowest in the dimension of rejection. Conclusion: The findings indicated that the implementation of the program for educating elderly respect in family was effective in abuse reduction. Therefore, training elderly respect programs are recommended. Also, clarification of this phenomenon from different aspects is better to be considered as a priority